Cloning a eukaryotic DNA glycosylase repair gene by the suppression of a DNA repair defect in Escherichia coli. - Chen, J (1989)
If eukaryotic genes could protect bacteria with defects in DNA repair, this effect could be exploited for the isolation of eukaryotic DNA repair genes. We have thus cloned a DNA repair gene from Saccharomyces cerevisiae that directs the synthesis of a DNA glycosylase that specifically releases 3-methyladenine from alkylated DNA and in so doing protects alkylation-sensitive Escherichia coli from killing by methylating agents. The cloned yeast gene was then used to generate a mutant strain of S. cerevisiae that carries a defect in the glycosylase gene and is extremely sensitive to DNA methylation. This approach may allow the isolation of a large number of eukaryotic DNA repair genes.